2022
DOI: 10.3390/electronics11050724
|View full text |Cite
|
Sign up to set email alerts
|

Relation between Student Engagement and Demographic Characteristics in Distance Learning Using Association Rules

Abstract: Distance learning has made learning possible for those who cannot attend traditional courses, especially in pandemic periods. This type of learning, however, faces a challenge in keeping students engaged and interested. Furthermore, it is important to identify students who are in need of help to ensure that their progress does not deteriorate. First, the research identifies students’ engagement based on their behaviors in Virtual Learning Environment (VLE) and their performances in assessments. This research g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…It was found that student engagement differs by gender (Sontam & Gabriel, 2012). The study of Jawthari and Stoffa (2022) also established the gender difference in student engagement in learning. It was determined whether the amount of time and energy invested in educational practices differed between students from different racial and ethnic groups (Greene et, al.…”
Section: Resultsmentioning
confidence: 89%
“…It was found that student engagement differs by gender (Sontam & Gabriel, 2012). The study of Jawthari and Stoffa (2022) also established the gender difference in student engagement in learning. It was determined whether the amount of time and energy invested in educational practices differed between students from different racial and ethnic groups (Greene et, al.…”
Section: Resultsmentioning
confidence: 89%
“…By using different types of software, student flexibility was also trained. In addition, using the software can increase students' interest in studying and motivation, which is no less important [44], [45]. A detailed description of the model is given in the study [41].…”
Section: Figure 3 Entrance Test Resultsmentioning
confidence: 99%
“…The formal definition of an association rule, as stated in [49], is as follows: Let A = {s1, s2, ..., sx} be a set of d attributes referred to as items, and B = {t1, t2, ..., ty} be a set of y transactions known as the database. Each transaction ts in B consists of a subset of the items in A.…”
Section: Association Rule Miningmentioning
confidence: 99%
“…To discover the interesting associative patterns, FP-Growth association rules mining algorithm was implemented using python programming language. In order to transform the dataset into a binomial structure that is compactible for the adopted FP-Growth Association rule mining algorithm each EI score was transformed into one of the following categories: poor (0-29), good (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) or excellent (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60) depending on the EI score on the rescaled 60-point scale. This representation is consistent with the student academic performance grading system of both universities, with fails (0-49), passes and distinction (75-100).…”
Section: Association Rule Miningmentioning
confidence: 99%